Contribution of soil bacteria to the atmosphere across biomes - Stephen D.J. Archer; Kevin C. Lee; Tancredi Caruso; Antonio Alcami; Jonathan G. Araya; S. Craig Cary; Don A. Cowan; Claudia Etchebehere; Batdelger Gantsetseg; Benito Gomez-Silva; Sean Hartery; Ian D. Hogg; et al. (Science of The Total Environment, 2023)

Hypolithic and soil microbial community assembly along an aridity gradient in the Namib Desert - Francesca Stomeo; Angel Valverde; Stephen B. Pointing; Christopher P. McKay; Kimberley A. Warren-Rhodes; Marla I. Tuffin; Mary Seely; Don A. Cowan (Extremophiles, 2013)

Hypolithic microbial communities: between a rock and a hard place - Yuki Chan; Donnabella C. Lacap; Maggie C. Y. Lau; Kong Ying Ha; Kimberley A. Warren‐Rhodes; Charles S. Cockell; Donald A. Cowan; Christopher P. McKay; Stephen B. Pointing (Environmental Microbiology, 2012)
Summary Drylands are the largest terrestrial biome on Earth and a ubiquitous feature is desert pavement terrain, comprising rocks embedded in the mineral soil surface. Quartz and other translucent rocks are common and microbial communities termed hypoliths develop as biofilms on their ventral surfaces. In extreme deserts these represent major concentrations of biomass, and are emerging as key to geobiological processes and soil stabilization. These highly specialized communities are dominated by cyanobacteria that support diverse heterotrophic assemblages. Here we identify global‐scale trends in the ecology of hypoliths that are strongly related to climate, particularly with regard to shifts in cyanobacterial assemblages. A synthesis of available data revealed a linear trend for colonization with regard to climate, and we suggest potential application for hypoliths as ‘biomarkers’ of aridity on a landscape scale. The potential to exploit the soil‐stabilizing properties of hypolithic colonization in environmental engineering on dryland soils is also discussed.

Cyanobacteria and chloroflexi-dominated hypolithic colonization of quartz at the hyper-arid core of the Atacama Desert, Chile - Donnabella C. Lacap; Kimberley A. Warren-Rhodes; Christopher P. McKay; Stephen B. Pointing (Extremophiles, 2011)

Hypolithic community shifts occur as a result of liquid water availability along environmental gradients in China's hot and cold hyperarid deserts - Stephen B. Pointing; Kimberley A. Warren‐Rhodes; Donnabella C. Lacap; Kevin L. Rhodes; Christopher P. McKay (Environmental Microbiology, 2007)
Summary Hypolithic cyanobacterial communities occur in hot and cold hyperarid environments but the physical factors determining their diversity are not well understood. Here we report hypolithic diversity and colonization of a common quartz substrate at several hyperarid locations in the ancient deserts of north‐western China, that experience varying mean annual temperature, rainfall and concomitant availability of liquid water in soil. Microscopy and enrichment culture resulted only in Chroococcidiopsis morphotypes which were ubiquitous, but community phylogenetic analysis revealed considerable cyanobacterial and heterotrophic bacterial diversity. Species Richness and Shannon's Diversity Index displayed a significant positive linear correlation with availability of liquid water but not temperature or rainfall alone. Several taxonomic groups occurred only in specific climatically defined locations, while for Chroococcidiopsis , Deinococcus and Phormidium location specific lineages within these genera were also evident. Multivariate analysis was used to illustrate pronounced community shifts due to liquid water availability, although these did not significantly affect the predicted functional relationships within any given assemblage in either hot or cold, wet or dry hyperarid deserts. This study clearly demonstrates that availability of liquid water, rather than temperature or rainfall per se is the key determinant of hypolithic diversity in hyperarid locations, and furthermore that functionally similar yet taxonomically distinct communities occur, characterized by the presence of taxa that are specific to defined levels of aridity.